Associations Among PCSK9 Levels, Atherosclerosis-Derived Extracellular Vesicles, and Their miRNA Content in Adults With Obesity - Macchi, Chiara; Greco, Maria Francesca; Favero, Chiara; Dioni, Laura; Cantone, Laura; Hoxha, Mirjam; Vigna, Luisella; Solazzo, Giulia; Corsini, Alberto; Banach, Maciej; Pesatori, Angela C.; Bollati, Valentina; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Extracellular vesicles (EV) concentration is generally increased in patients with cardiovascular diseases, although the protective role of EVs in atherosclerosis has been reported. Among the specific cargo of EVs, miRNAs contribute to different stages of atherosclerosis. Aim of the present report has been to investigate, in individuals with obesity, the interplay among EVs derived from cells relevant for the atherosclerotic process (i.e., platelets, endothelium, monocytes/macrophages, and neutrophils), their miRNA content and proprotein convertase subtilisin/kexin type 9 (PCSK9), one of the main regulators of low-density lipoprotein receptor (LDLR). Methods and Results: EVs have been isolated from 936 individuals with obesity (body mass index = 33.6 ± 5.6 Kg/m2) and a raised cardiovascular risk (e.g., LDL-C = 131.6 ± 36.4 mg/dL, HOMA-IR = 3.1, and roughly 50% on anti-hypertensive medications). PCSK9 levels were negatively associated with EV count in the range 150–400 nm and with those derived from macrophages (CD14+), endothelium (CD105+), and neutrophils (CD66+). The association between PCSK9 and platelet-derived EVs (CD61+) was modified by platelet counts. PCSK9 was significantly associated with five EV-derived miRNAs (hsa-miRNA−362−5p,−150,−1244,−520b-3p,−638). Toll-like receptor 4 and estrogen receptor 1 were targeted by all five miRNAs and LDLR by four. The effect on LDLR expression is mainly driven by hsa-miR-150. Considering the implication of EV in atherosclerosis onset and progression, our findings show a potential role of PCSK9 to regulate EV-derived miRNAs, especially those involved in inflammation and expression of low-density lipoprotein receptor (LDLR) receptor.